Analysis of the Cultural Impact on Practicing Islamic Values toward Community Behavior in Turi Village, Panekan District - Yana Dwi Christianti (International Journal of Religion, Humanity and Cultural Heritage, 2025)
Indonesia has a unique position as the country with the largest Muslim population in the world, marked by a wealth of diverse local cultures. History records that the spread of Islam in Indonesia occurred peacefully through a process of acculturation, rather than conquest, resulting in a distinctive integration with local traditions. The arrival of Islam, with all its cultural components, successfully garnered the sympathy of the majority of the Indonesian people, and Islam was accepted into the local cultural landscape that had long been rooted in the archipelago. Cultural elements in Indonesia not only coexist with Islamic values but actively mediate their implementation, shaping various aspects of societal behavior. The Islamic cultural values in Indonesia can be packaged in such an appealing way that people do not realize that these Islamic values have become traditions in their daily lives. Islam has brought changes in various aspects of life, such as art, language, architecture, and ways of dressing, playing a role in integrating these cultural elements into a broader Islamic context.